Pengaruh Pola Pemberdayaan Berpikir Melalui Pertanyaan dalam Pembelajaran Team Game Tournament terhadap Kemampuan Kognitif, Sikap IPA dan Kesadaran Metakognitif Siswa - Zuhriyatur Rosyidah; Siti Zubaidah; Susriyati Mahanal (Universitas Negeri Malang, 2015)
Abstract: The research aim to examine effect of Thinking Empowerment by Questioning pattern in Team Game Tournament (TEQ-TGT) towards cognitive ability, science attitude, and metacognitive awareness of students in Grade 8 SMP Negeri 2 Ponorogo. The research used a quasi experimental method with pretest posttest only controls group design. The datas were obtained from cognitive test, questionnaire of Likert Scale, and Metacognitive Awareness Inventory (MAI) questionnaire. The results showed that there were differences of effect in cognitive ability, science attitude, and me-tacognitive awareness of students that using learning patterns TEQ-TGT than the students who TEQ pattern. Key Words: TEQ-TGT, cognitive ability, acience attitude, metacognitive awareness Abstrak: Penelitian ini bertujuan untuk mengetahui perbedaan pengaruh pola pembelajaran PBMP-TGT terhadap kemampuan kognitif, sikap IPA, dan kesadaran metakognitif siswa kelas 8 SMP Negeri 2 Ponorogo. Penelitian ini menggunakan eksperimen semu dengan desain pretest posttest only con-trol group design. Data diperoleh dari hasil pretest dan posttest kemampuan kognitif, angket Skala Likert, dan Angket Metacognitive Awareness Inventory (MAI). Hasil penelitian menunjukkan ada perbedaan pengaruh kemampuan kognitif, ada perbedaan pengaruh sikap IPA dan kesadaran metakog-nitif siswa yang dibelajarkan dengan menggunakan pola pembelajaran PBMP-TGT dengan siswa yang dibelajarkan dengan pola PBMP. Kata kunci: PBMP-TGT, kemampuan kognitif, sikap IPA, kesadaran metakognitif